2011
DOI: 10.1007/s00192-011-1429-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for urinary tract infection following incontinence surgery

Abstract: Introduction and Hypothesis The purpose of this study is to describe risk factors for post-operative urinary tract infection (UTI) the first year after stress urinary incontinence surgery. Methods Multivariable logistic regression analyses were performed on data from 1,252 women randomized in two surgical trials, Stress Incontinence Surgical Treatment Efficacy Trial (SISTEr) and Trial Of Mid-Urethral Slings (TOMUS). Results Baseline recurrent UTI (rUTI; ≥ 3 in 12 months) increased the risk of UTI in the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
4
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 18 publications
2
35
4
4
Order By: Relevance
“…This analysis found that a history of recurrent UTIs preoperatively was the strongest risk factor for postoperative UTI [8]. Our study confirmed a similar association between a history of recurrent UTIs and preoperative UTI.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This analysis found that a history of recurrent UTIs preoperatively was the strongest risk factor for postoperative UTI [8]. Our study confirmed a similar association between a history of recurrent UTIs and preoperative UTI.…”
Section: Discussionsupporting
confidence: 89%
“…Urinary tract infections (UTIs) are the second most common infection in older women, representing 25% of all clinically diagnosed infections in the US [4]. It is one of the most commonly reported complications of pelvic reconstructive surgery with an estimated incidence as high as 24% [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…30,33,34 In our population, the use of D10 was associated with a 22% increase in UTI with a number needed to harm of 4.5 (absolute rate in D10 group of 47.8%). Patients whose cystoscopy was performed with D10 had a 3.4 times greater odds of being treated for a UTI in the 6 weeks following surgery, even after adjusting for a history of prolonged postoperative catheterization and preoperative recurrent UTI, which are among the most modifiable risk factors of postoperative UTI in patients undergoing urogynecological procedures.…”
Section: Commentmentioning
confidence: 74%
“…Patients whose cystoscopy was performed with D10 had a 3.4 times greater odds of being treated for a UTI in the 6 weeks following surgery, even after adjusting for a history of prolonged postoperative catheterization and preoperative recurrent UTI, which are among the most modifiable risk factors of postoperative UTI in patients undergoing urogynecological procedures. 34 This is a substantial increase and clinically relevant.…”
Section: Commentmentioning
confidence: 98%
“…The higher rate of UTIs in the mesh group was likely associated with the higher rates of retention and associated catheterizations, both known to predispose patients to UTIs. [25][26][27] Mesh placement was associated with higher rates of UTIs, regardless of concomitant sling placement. A UTI diagnosis appearing in a Medicare claim may or may not be culture-proven.…”
Section: Commentmentioning
confidence: 96%